Documenting disappearance: self-forgery and dissimulation as a means of mobility. - Campanioni, Chris (Social Identities, 2022)
How have migrants and other displaced and internally excluded persons used dissimulation and self-forgery in service of mobility? How can we read an aesthetics of disappearance as more than just an aesthetical choice but as a source of activism? Following Jacques Rancière [The politics of aesthetics (G. Rockhill. Trans.). Continuum. (Original Work Published in, 2000)], I understand that such aesthetic acts are capable of creating 'new modes of sense perception' and, in doing so, produce alternative forms of political subjectivity. In this essay, I compare migrant self-representations and creative tactics of camouflage, mimicry, and dissembling with public practices, while looking at the extraterritorial space of the makeshift camp as a paradigm for preserving invisibility and anonymity. And yet, it is not just that aesthetic acts have the potential to produce novel forms of political subjectivity, as Rancière understood, but that, in order for the latter to be true, the equation needs to be reversed: political subjects must first be recognized as aesthetic subjects. As I place the multimedia work of Cold War East German artist Cornelia Schleime in conversation with the contemporary glitch art – drawings, paintings, video – of Kon Trubkovich, who was born in Moscow and left, at age eleven, following the Chernobyl disaster, I argue that to reorient the terms of visibility, it becomes necessary for subject-producers to stage the gaze that would otherwise objectify them.